Analisis Pelayanan Prima pada Klinik ABC - Safira Hasan, Elsya; Christian Wiradendi Wolor; Adnan Kasofi (Journal Of Accounting and Business, 2024)
This study is a qualitative study with a descriptive approach that focuses on observing phenomena or events in original conditions. The researcher uses primary and secondary data collection. The data collected for this study were collected directly from the source through observation, documentation, and interview data collection techniques. The purpose of this study was to determine the implementation, obstacles and recommended solutions for excellent service at the ABC Clinic. This study uses the theory of Miles and Huberman regarding interactive model data analysis. Based on the study's results, it can be seen that the implementation of excellent service at the ABC Clinic is good. However, some patients and service officers still feel that there are obstacles. These obstacles include the lack of human resources, unfriendly officers, and differences in understanding between patients and medical officers. From these obstacles, there are several recommended solutions, namely opening job vacancies, participating in facilitated training, and improving good communication techniques.